Pseudocapacitive materials for energy storage: properties, mechanisms, and applications in supercapacitors and batteries - Wei, Yi-Min; Kumar, Kulurumotlakatla Dasha; Zhang, Long; Li, Jian-Feng (Frontiers in Chemistry, 2025)
The growing demand for efficient energy storage has intensified interest in pseudocapacitive materials, known for their high-power density, rapid charge–discharge capabilities, and tunable physicochemical properties. This review explores the foundational principles and evolution of pseudocapacitive materials, emphasizing recent strategies to improve their electrochemical performance in supercapacitor applications. Key focus areas include: 1) intercalation-type materials such as Nb2O5, TiO2, and V2O5, which offer fast and reversible ion insertion without phase transitions; 2) redox-active materials like transition metal oxides and 2D materials (e.g., MXenes), which enhance charge storage through surface and near-surface Faradaic reactions; and 3) materials relying on surface adsorption mechanisms that enable ultrafast kinetics and excellent cycling stability. Special attention is given to nickel-based compounds NiO, Ni(OH)2, and related composites owing to their high theoretical capacitance, multiple valence states, and cost-effectiveness, making them promising for both supercapacitors and hybrid energy storage devices. The interplay between structural design, conductivity, and electrochemical behavior is critically assessed. Lastly, the review outlines current challenges and future directions in the development of scalable, high-performance pseudocapacitive materials. This work aims to guide the rational design of next-generation electrode materials for advanced supercapacitor technologies.